2016
DOI: 10.1016/j.tre.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Shipping investor sentiment and international stock return predictability

Abstract: Stock return predictability by investor sentiment has been subject to constant updating, but reaching a decisive conclusion seems rather challenging as academic research relies heavily on US data. We provide fresh evidence on stock return predictability in an international setting and show that shipping investor sentiment is a common leading indicator for financial markets. We establish out-of-sample predictability and demonstrate that investor sentiment is also economically significant in providing utility ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“… Grammenos and Arkoulis (2002) have shown that oil prices, laid up tonnage and exchange rates affect the shipping industry. Likewise, Papapostolou et al, 2014 , Papapostolou et al, 2016 show that industrial production and cumulative crisis periods in Asia and in the G7 countries are acting as indicators of the international demand for shipping services. Finally, oil prices have extensively being linked with the shipping markets as they have a lead-lag relationship with the freight rates ( Angelopoulos et al, 2020 ) and thus they can provide better forecasts for the tanker and the dry bulk market ( Gavriilidis et al, 2018 ; Michail, 2020 ).…”
Section: Review Of the Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“… Grammenos and Arkoulis (2002) have shown that oil prices, laid up tonnage and exchange rates affect the shipping industry. Likewise, Papapostolou et al, 2014 , Papapostolou et al, 2016 show that industrial production and cumulative crisis periods in Asia and in the G7 countries are acting as indicators of the international demand for shipping services. Finally, oil prices have extensively being linked with the shipping markets as they have a lead-lag relationship with the freight rates ( Angelopoulos et al, 2020 ) and thus they can provide better forecasts for the tanker and the dry bulk market ( Gavriilidis et al, 2018 ; Michail, 2020 ).…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…We are building our model not only by introducing for the first time a quantifiable variable for the exogenous event but also by using additional variables that are acting as proxies for the global supply and demand of the shipping markets. Additionally, so as to exclude any potential spillovers that may have erupted between economy and the shipping markets, we are including variables of that are connecting the outcome of the event to the financial markets, since the relationship that exists between the two is already well-established ( Kavussanos et al, 2014 ; Papapostolou et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Menkhoff and Rebitzky [50] mention that, in the long run, exchange rates move in a fundamental direction while investor sentiment continues to build unreasonable currency rate expectations. It is also indicated that investor sentiment in the stock market only has a short-lived effect on the exchange rate, while in the long term, investor sentiment is cointegrated with fundamental factors such as interest rate and inflation [51]. Furthermore, Uhl [52] insists that news sentiment in the stock market has nothing to do with exchange rate return.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kawasaki and Matsuda (2014) developed a logit-based model to forecast container and bulk shipping for wood pulp transport between East Asia and the USA. Li et al (2018), Papapostolou et al (2016) and Papapostolou et al (2014) examined the sentiment index for future demand forecasting in the shipping industry and identified as having a significant impact. However, to the best of our knowledge, no study to date has measured the impact and durability of economic indicators on container movement.…”
Section: Durability Of Economic Indicatorsmentioning
confidence: 99%